Stability Enhancement of DFIG Wind Farm Using SSSC With FOPID Controller - Chethan Hiremarali Ramalingegowda; Mageshvaran Rudramoorthy (IAES Indonesian Section, 2023)
The wind power generation has become more important nowadays to meet the increase in power demand. DFIG based wind power generation is the recent and used in many countries due to its better power controllability. The controllers like Proportional Integral (PI) are used for the stabilization of the waveforms of the supply system. The change in controllers produces better oscillation damping in recent days. The effect of varying the wind input to generate power using the wind turbine resulting in instability in the power system because of the control is done on a grid supply. This paper aims to proposes an optimum FOPID controller for damping power system instability using a Static Synchronous Series Compensator (SSSC) system that takes into account the dynamics of wind energy conversion systems (WECS) connected to a infinite grid. The WECS model, which includes variations in wind supply to the wind turbine, has been developed to test the durability of the optimized controller that was developed to damping power system oscillations. The controller used to take the power system dynamics into account. A new controller is being designed to include a corrective measure for the damping the oscillations to adjust the instability caused by wind supply variations. The controller helps to tune the controller settings that lead to the achievement of the power oscillation damping objectives. These results are compared with conventional PMSM based wind turbine system.